PENGARUH UKURAN PERUSAHAAN, REPUTASI AUDITOR, KOMITE MANAJEMEN RISIKO, KOMISARIS INDEPENDEN, DAN KONSENTRASI KEPEMILIKAN TERHADAP PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT - Anggi Anindya Ramadhani, 13.05.52.0096; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2017)
This study aimed to examine the effect of Firm Size, Auditor Reputation, Risk Management Committee, Independent Commissioners, and Ownership Concentration ofEnterprise Risk Management. This study focused on manufacturing companies listed in Indonesia Stock Exchange (BEI) period 2013-2015. This study 177 number of observations sample obtained by the method nonprobability sampling purposive sampling technique. The analysis technique used in this research is multiple linear regression analysis. The analysis showed that the Auditor Reputation, Risk Management Committee, and Independent Commissionershasno effect on Enterprise Risk Management. Firm Size and Ownership Concentration has effect on Enterprise Risk Management.Keywords: Enterprise Risk Management, Firm Size, Auditor Reputation, Risk Management Committee, Independent Commissioners, and Ownership Concentration